A network meta‐analysis to compare glycaemic control in patients with type 2 diabetes treated with exenatide once weekly or liraglutide once daily in comparison with insulin glargine, exenatide twice daily or placebo. Issue 3 (3rd October 2012) - Scott, D. A.; Boye, K. S.; Timlin, L.; Clark, J. F.; Best, J. H.
Abstract Aims The glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) exenatide once weekly (ExQW) and liraglutide once daily (QD) are indicated to improve glycaemic control in patients with type 2 diabetes. Although glycaemic control with ExQW versus liraglutide QD 1.8 mg has been directly compared, no studies have compared ExQW with liraglutide QD 1.2 mg or determined the probable relative efficacies of various injectable therapies for glycaemic control; therefore, a network meta‐analysis was performed to address these questions. Methods A systematic review identified randomized controlled trials of ≥24 weeks that compared ExQW, liraglutide QD (1.2 mg, 1.8 mg), insulin glargine, exenatide twice daily (ExBID), or placebo. Twenty‐two studies evaluating 11 049 patients were included in the network meta‐analysis. Mean differences in HbA1c relative to placebo or each other and probability rankings were estimated. Results Estimated mean differences in HbA1c versus placebo were −1.15% (95% CrI: −1.31 to −1.00) for ExQW, −1.01% (95% CrI: −1.18 to −0.85) for liraglutide 1.2 mg, and −1.18% (95% CrI: −1.32 to −1.04) for liraglutide 1.8 mg. HbA1c differences for ExQW versus liraglutide 1.2 mg and 1.8 mg were −0.14% (95% CrI: −0.34 to 0.06) and 0.03% (95% CrI: −0.14 to 0.18), respectively. The estimated mean difference in HbA1c between liraglutide 1.2 mg and 1.8 mg was 0.17% (95% CrI: 0.02–0.30). Results were consistent when adjusted for background antihyperglycaemic medications and diabetes duration. Conclusions This network meta‐analysis did not identify meaningful differences in HbA1c lowering between ExQW and both liraglutide doses, suggesting that these GLP‐1 RAs have similar glycaemic effects.